ENSURING INFORMATION SECURITY IN ACCOUNTING AND AUDIT IN UZBEKISTAN: RISKS IN DIGITAL SYSTEMS AND THEIR MANAGEMENT - Avilov Nematjon , Yuldashevich (THE INNOVATION ECONOMY, 2025)
This article analyzes information security in digital accounting and auditing systems in Uzbekistan. The study examines cyber risks (data theft, system failures) and the effectiveness of countermeasures (encryption, internal controls). A mixed-methods approach was employed, combining qualitative analysis (of legislation and enterprise documents) and quantitative analysis (of cyber threat statistics for 2020–2024). Findings indicate improved data protection due to security measures, but highlight challenges such as insufficient skills, financial constraints, and infrastructure limitations. Practical recommendations tailored to Uzbekistan’s context are provided.